Topsis multiple attribute decision support analysis for supplier selection problem in a group decision making / Omid Jadidi, Rosnah Mohd Yussuff and Fatemeh Firouzi - Jadidi, Omid; Mohd Yussuff, Rosnah; Firouzi, Fatemeh (2008)
Supplier selection is a multiple attribute decision making (MADM) problem that must be done in a group decision making. Since the decision makers' (DMs) preferences on alternatives or attributes of suppliers are often uncertain, supplier selection becomes more difficult, and the impact of the DMs priority on the decision making must be considered. TOPSIS (technique for order performance by similarity to ideal solution) method is one of the methods used to study uncertainty. In this paper, the TOPSIS approach has been used to deal with the supplier selection problem in a group decision making and consider relative importance of each DM. The work procedure is as follows: firstly, the weighs and ratings of attributes for all supplier alternatives are described by each DM. Secondly, relative importance of each DM is considered to establish the decision matrix. Thirdly, the separation measure is used to determine the ranking order of all alternatives of supplier, and then a linear programming model is established to find the optimum order quantities. Finally, an example of a selection problem of supplier is used to illustrate the proposed approach.